Revisiting Between-group Inequality Measurement : An Application to the Dynamics of Caste Inequality in Two Indian villages - Lanjouw, Peter; Rao, Vijayendra (2012)
Standard approaches to decomposing how much group differences contribute to inequality rarely show significant between-group inequality, and are of limited use in comparing populations with different numbers of groups. This study applies an adaptation to the standard approach that remedies these problems to longitudinal household data from two Indian villages -- Palanpur in the north, and Sugao in the west. The authors find that in Palanpur the largest scheduled caste group failed to share in the gradual rise in village prosperity. This would not have emerged from standard decomposition analysis. However, in Sugao the alternative procedure did not yield any additional insights because income gains applied relatively evenly across castes.